Overview the Quality of Popular Hadith about Isra' Mi'raj in the Book of Dardir 'Ala Qishatul Mi'raj - Afriandi Tanjung; Nofri Andy.N (Jurnal Living Hadis, 2022)
This article examines the quality of the popular hadith about Isra 'Mi'raj contained in the book Dardir 'Ala Qishatul Mi'raj. This hadith is often used by preachers without first examining the quality of the hadith. This problem is then investigated through library research. In processing the data the author uses the takhrij al-hadith method, which is tracing the hadith that the author will examine into the original source in order to find out how the quality of the hadith studied is. The results of this study explain that the quality of the hadith which consists of three popular hadiths about Isra' Mi'raj contained in the book Dardir 'Ala Qishatul Mi'raj is of Hasan quality. The syarah of the hadith reveals that there has been a cleavage of the Prophet's chest which was then filled with faith and wisdom, the command to pray and about Sidratul Muntaha at which time the Prophet was given three things, namely the command to pray, closing the letter Al-Baqarah and forgiveness of sins for those who do not associate Allah Swt.